An approach to the Urgencies and Emergencies Medicine - Jorge Luis Sánchez Guillaume (Centro Provincial de Información de Ciencias Médicas, 2018)
A study on the development of the Urgencies and Emergencies Medicine, its main concepts and peculiarities is carried out. The current pattern of the SIUM  in Cuba is approached, which has been the solution to the severely-ill patient and it has allowed to offer care in a fast and qualified way according to the demands of this service, which is characterized by the detection, access, basic and advanced vital support and access to the intensive cares.